Decoding Mandibular Angle Fracture Management: Biomechanical Analysis of Different Plating Techniques – An In Vitro Study - Adalarasan Subramanian; Thiruneelakandan Sambanthan; Akash Punithan; S Meera Petchiammal; R. Bhuvana Laxmi; Vishal Srikanth; E Eswar (Journal of Pharmacy and Bioallied Sciences)
Objective: The primary rationale of the study is to assess the biomechanical aspects of Champy’s, monoplanar, biplanar, and 3D strut plating systems using an in vitro model in the management of the angle of mandible fracture. Methods: Thirty-two hemi-sectioned mandibles (N = 32) were obtained from adult goats and divided into four groups (N = 8) for different plating techniques: monoplanar, biplanar, Champy’s, and three-dimensional curved angle strut plating. A customized biomechanical test machine simulated masticatory loads by applying compressive forces. Force versus displacement data were recorded using an Instron Lloyd LRX machine. Results: Plating techniques with two plates exhibited higher resistance to displacement than single-plate techniques. The three-dimensional curved angle strut plate group had the highest mean compressive strength (184.7913 N), followed by biplanar plating (170.29 N), monoplanar plating (159.3419 N), and Champy’s plating (55.48375 N). Statistical analysis showed significant differences between the three-dimensional curved angle strut plating technique and Champy’s plating technique (P value ≤ 0.0016*), as well as between the biplanar plating technique and Champy’s plating technique (P value ≤ 0.0010*). Conclusion: The three-dimensional curved angle strut plate and biplanar plating techniques exhibited superior biomechanical performance compared to monoplanar and Champy’s plating techniques.